SAE Technical Paper Series 2002
DOI: 10.4271/2002-01-2752
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Changing Fuel Path Dynamics in Twin-Independent Variable Camshaft Timing Engines

Abstract: The effect of a variable camshaft timing (VCT) disturbance on air-to-fuel ratio (AFR) signal is investigated for a twin-independent (TI) VCT engine. Different types of VCT disturbances on AFR signal are investigated. Gaseous fuel experiments are performed in addition to conventional petrol fuel experiments to show that not all the transient VCT disturbances acting on AFR are due to changes in air path dynamics. Experiments show that varying exhaust valve closing (EVC) timing has a significant effect on the air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a conventional engine air flow transients can be generated by rapidly opening or closing the throttle (Mancini, Pursifull and Kotwicki, 1996). A recent experimental study has shown that air charge transients can be generated by step changes in the valve overlap timing (Genc, Ford, Glover and Collings, 2002). In a camless engine, during events that require large step changes in the valve timing, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a conventional engine air flow transients can be generated by rapidly opening or closing the throttle (Mancini, Pursifull and Kotwicki, 1996). A recent experimental study has shown that air charge transients can be generated by step changes in the valve overlap timing (Genc, Ford, Glover and Collings, 2002). In a camless engine, during events that require large step changes in the valve timing, e.g.…”
Section: Introductionmentioning
confidence: 99%